Gastrointestinal Bleeding as a Manifestation of IntestinalTuberculosis in Leprosy Patients with Reversal Reaction andHistory of Long-Term Steroid Therapy - Gebrina, Meutia; Nursyirwan, Saskia Aziza; Soewondo, Pradana; Fauzi, Achmad; Renaldi, Kaka (UI Scholars Hub, 2016)
Intestinal tuberculosis is difficult to be diagnosed. Signs and symptoms usually are not specific, and the results of diagnostic tools are frequently negative. One of the unusual symptoms of intestinal tuberculosis is gastrointestinal bleeding, which should increase the awareness of clinical practitioners.